Mineral profiling of Turkish wheat genetic resources unveiled their conserved potential for biofortification in combating hidden hunger - Aktas, Husnu; Nadeem, Muhammad Azhar; Tutus, Yusuf; Dogan, Serap; Karaman, Mehmet; Erdemci, Irfan; Wang, Meng-Lu (Springer, 2024)
Micronutrient deficiencies, also known as hidden hunger, pose a threat to the global population alongside food scarcity. Wheat is a staple food for a huge population and available commercial cultivars generally lack sufficient mineral contents. Crop wild relatives harbor novel variation crucial for crop improvement programs including biofortification. The southeastern region of T & uuml;rkiye is blessed with diverse wheat germplasm. This study aimed to explore the mineral content diversity in different wheat species germplasm; i.e., Triticum boeoticum, T. dicoccoides, T. durum, and T. aestivum. Various mineral elements; i.e., Zn, Fe, K, P, S, Mg, Ca, and Mn were investigated in the grains of 192 genotypes. The analysis of variance (ANOVA) results showed highly significant genotypic effects of all traits in T. boeoticum, T. dicoccoides, and T. durum. The highest seed Zn concentration (77.8 mg kg-1) was found in T. boeoticum genotype-36 and the lowest (24.9 mg kg-1) was recorded in genotype T. aestivum genotype-4. A total of 16 genotypes belonging to T. dicoccoides had > 50 mg kg-1 grain Zn content and can be a potential source for developing Zn-enriched durum wheat cultivars. Maximum Fe content (109 mg kg-1) was found in T. dicoccoides genotype-11, while minimum (29 mg kg-1) was recorded in T. durum genotype-55. Zinc and Fe contents in T. boeoticum and T. dicoccoides genotypes were found more than twice as reported previously with T. durum and bread wheat germplasm. Grain Zn contents showed a highly significant and positive correlation with the various studied traits. Principal components analysis (PCA) and biplot confirmed that first two principal components accounted for a total of 79.14% variation. The present investigation confirmed that available bread wheat's genetic resources have low genetic diversity and its wild relatives conserve unexplored variation that can be helpful for wheat biofortification.
Keywords: T. boeoticum; Tr. dicoccoides; T. durum; Mineral profiling; Wild relatives; Germplasm characterization